Sargentgloryvine Stem Water Extract Mediated Nrf2 Pathway Activation and HO-1 Upregulation - Zhaorong CHEN; Xiaoping CHENG; Jianfeng CHU; Jun PENG; Wei LIN (康复学报)
Objective:To investigate the protective effect of Sargentgloryvine stem extract (SSE) against oxidative stress by regulating Nrf2 signal pathway and anti-oxidative stress related protein HO-1 expression of human monocyte cell line U937.Methods:U937 cells were pretreated by PMA and randomly assigned to control group, LPS stimulated which was stimulated with 1 μg/mL LPS, and LPS+SSE treated group which was stimulated with 1 μg/mL LPS and treated with SSE. Morphologic changes of the cells were observed by microscopy, mRNA expression of Nrf2 were detected by Real-time PCR, and the protein expression was detected by protein electrophoresis and immunoblotting, Nrf2 translocation to nuclear was observed by immunofluorescence staining observation.Results:1 mg/mL of SSE treatment significantly enhanced Nrf2 gene transcription (P<0.01). Immunoblot detected by antibodies recognizing Nrf2, Keap1, and HO-1 upregulation of Nrf2 and HO-1, and downregulation of Keap1 protein. Immunofluorescence images indicated that SSE treatment increased Nrf2 translocation into nuclear.Conclusion:SSE was able to activate Nrf2 signal pathway by increasing Nrf2 expression, and suppressing Keap1, which in turn increased Nrf2 translocation into nuclear and unregulated HO-1 expression.